Prospective memory assessment: Scientific advances and future directions - Blondelle, Geoffrey; Sugden, Nicole; Hainselin, Mathieu (Frontiers in Psychology, 2022)
Prospective Memory (PM), the ability to remember to realise intended actions in the future, is crucial for maintaining autonomy. Decades of research has focused on a so-called age PM paradox, where older adults outperformed younger adults on some PM tasks, but not others. Contributing to this paradox is heterogeneity in and a lack of valid assessment methods. Previous research showed a lack of convergent validity between performance-based PM and both self-report and informant-report measures. We argue that questionnaires may be relevant to obtain information regarding patients’ awareness of their PM difficulties but need to be used in conjunction with performance-based tools. Within performance-based PM tools there are also difficulties in measurement: 15 to 60 minutes experimental tasks and batteries have a good reliability but cannot usually fit in a standard clinical evaluation, while shorter PM measures have lower reliability and sensitivity. In this perspective paper, we encourage researchers to develop more ecological and valid tools. Innovative PM paradigms that allow participants to generate their own intentions and that take task costs into consideration should be developed. Future research will also need to focus on cognitive factors, personality and online evaluation, to improve PM assessment and develop ad-hoc rehabilitation programs.